(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This study examined the role of women’s leadership in driving social and economic transformation through community action in Thiruvananthapuram, Kerala. Using a mixed-methods research design, the study combined survey data from 120 women with interviews, focus group discussions, and field observations to assess their participation, leadership roles, and contributions to grassroots development. The findings showed that women played a central role in coordination, financial management, awareness campaigns, and linking communities to government schemes. Their involvement enhanced confidence, financial independence, decision-making abilities, and rights awareness, resulting in wider community benefits such as improved access to services, stronger unity, and increased participation of women and girls in public activities. Despite facing constraints such as household burdens, gender stereotypes, and limited financial resources, women demonstrated strong leadership that contributed to meaningful social transformation. The study emphasizes the need for sustained training, institutional support, and gender-responsive policies to strengthen women’s community leadership and accelerate inclusive development.